Analisis Kinerja Karyawan Pada PT Paragon Techonology and Innovation - Tiara Rosita Putri; Efriyani Sumastuti; M. Fajar Darmaputra (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
This study examined the effectsl of workload, stress, job appraisal, professionalism, and skills on employee performance among workers at PT Paragon Technology and Innovation. Using the Yamane formula and purposive sampling methods, a total of 75 individuals were found. Workload lhas a strongl favorable impact lon employee performancel, citing SPSS data. lWork stress has al considerable beneficial impact on employee performance, as demonstrated by the computed lt value ofl 3.901 lwith la significance value ofl 0.001 <0.05.l This suggests that lH1 is acceptedl. The calculated t lvalue ofl 3.361 indicates that H2 is rejected. H3 is approved since lthe regression coefficient value of 3.383 (positive)l and the lsignificance value of 0.001l<0.05 show that work appraisals significantly improve employee performance. H4 is rejected, according to lthe regression coefficient value ofl 1.348 l(positive)l and lthe significance value ofl 0.182 > 0.05. The computed F value of 21.812, lwith a significance valuel of 0.000 > 0.05, indicates that lH4 is acceptedl; work evaluation, lprofessionalism, andl talents all positively impact employee performance at the same time. This demonstrates that skills significantly improve worker performance. At 3.343, the regression coefficient is positive and has a significance level lof 0.001 < 0.05l.